Application of a Panel Method in Performance Prediction of Cavitating and Non-cavitating Tip Loaded Propellers. (November 2015) - Su, Yiran; Kinnas, Spyros A
Abstract: A panel method is applied to predict the performance of tip loaded propeller with and without cavitation modeling. For fully wetted cases, the geometry of the wake is shown to be critical to the computational accuracy. To align the wake surface, two methods are proposed and the full wake alignment scheme behaves better then PSF2 alignment. The boundary layer correction can also improve the pressure distribution especially near the trailing edge region. Finally, for cavitating cases, the results based on full wake alignment tend to create larger cavitation region and higher cavitation thickness compared to results based on PSF2 alignment.